Diversification of Income Sources for Cocoa Farm Households : A Case Study of the Central West of Côte d'Ivoire - B. G. Jean Jacques Iritié; Fabrice Soukou Djaléga (Institut National Polytechnique Houphouët Boigny (INP-HB), 2015)
This paper is aimed at identifying complementary sources of income for cocoa farm households in the Central West of Côte d'Ivoire. Our methodology con- sists of four successive stages: (i) a need assessment of cocoa households and specificities of the study area through a participatory diagnosis in order to pro- pose potential income generating activities; (ii) a technical qualitative analysis of these activities; (iii) an analysis of the profitability and (iv) an analysis of their social acceptability. It appears that beekeeping and snail breeding are the most appropriate activities for this cocoa producing region. However, the results show that the lack of information and technical knowledge, the religious burdens and the high local illiteracy rate can constitute barriers to the imple- mentation of IGAs. Finally, as future prospects, we discuss the opportunity to combine horizontal diversification and vertical diversification (especially, cocoa processing) in order to give more added value to the sustainable cocoa produc- tion and to contribute to the industrial development of Ivorian economy.
Keywords: O13; Q12; Q13; 330; Cocoa farm households; vulnerability; income generating activities; diversification; Côte d'Ivoire